#YourNewsPage framing analysis of the 2025 midterm elections news stories published by TV Patrol on TikTok from July 2024 to February 2025 - Bustamante, Jose Martin Adrian D.
This study sought to determine how TV Patrol framed their news stories on the pre-campaign period of the 2025 midterm elections published on TikTok. This study described the frames used by TV Patrol in the election-related news stories published on TikTok, determined how these frames are influenced by the five filters of propaganda, and analyzed how the news stories are influenced both by the frame-building aspect of news production and the five filters of propaganda in the news production process of TV Patrol, integrating De Vreese’s (2005) Integrated Process Model of Framing with Herman and Chomsky’s (1988) Propaganda Model of Mass Communication. Through the use of both qualitative content analysis and semi-structured interview, the study revealed that the Conflict, Attribution of Responsibility, and Human Interest frames are the most prevalent thematic frames in the news stories analyzed. The prevalence of the mentioned frames are further interpreted through the connection of the frame-building aspect of news production to the five filters of propaganda.